In vitro Induction of bulblet production from Lilium longiflorum - امين, سامي كريم محمد; طه, فادية هشام; المختار, سراب عبد الهادي (Journal of Kerbala for Agricultural Sciences, 2015)
A study on the effect of Murashige and Skoog (MS) salt strength ( 1MS or ½ MS) ;concentrations of Benzyladenine (BA) ( 0 , 0.1 , 0.5 mg/l)and Naphthalene-acetic acid ( NAA) ( 0 ,0.1 ,0.2 ,0.5 mg/l) on bulblets production of Lilium longiflorum was applied at the plant tissue culture lab. belonging to Hort. Dept. /College of Agric./Univ. of Baghdad from June ,2013 to March, 2014 . Results could be summarized as follow : Number and diameter of bulblets were not affected by MS salt strength either full strength of MS or ½ MS ,while 1 MS increased the dry and fresh weight of bulblets ( 10.4 , 9.3 g ) respectively . MS medium supplemented with BA alone was not affected on bulblet characters .However , NAA at 0.1 mg /l increased No. and fresh weight of bulblets ( 6.6 bulblets /explant and 1.06 g ) respectively . The influence of interaction between BA X NAA concentrations significantly improved the bulblets characters , BA at 0.5 mg /l x NAA at 0.1 mg / l was superior on increasing the number of bulblets ( 8.35 bulblets / explant. ) . The interaction between MS salt strength X BA levels was significant in increasing bulbletNo .; the best response was recorded at 1 MS X 0.5 mg /l of BA ( 5.9 bulblets / explant ). The interaction between MS salt strength X NAA concentrations was significant in elevating bulblets number ; 1 MS X 0.1 mg /l of NAA was the most effective treatment in increasing the number of bulblets / explant ( 7.2 bulblets / explant ).